Beta blocker use correlates with better overall survival in metastatic melanoma patients and improves the efficacy of immunotherapies in mice. (4th March 2018) - Kokolus, Kathleen M.; Zhang, Ying; Sivik, Jeffrey M.; Schmeck, Carla; Zhu, Junjia; Repasky, Elizabeth A.; Drabick, Joseph J.; Schell, Todd. D.
ABSTRACT: Immunotherapy has expanded treatment options for cancers with historically poor outcomes, yet a significant proportion of patients still fail to achieve durable clinical benefit. We defined the contribution of β-adrenergic receptor (βAR) signaling, a component of the stress response, on success of immunotherapy for melanoma since the use of antagonists (β-blockers) is associated with improved clinical outcomes in some cancers. We show that metastatic melanoma patients who received immunotherapy had improved overall survival if they also received pan β-blockers. This retrospective analysis is reinforced by results showing that βAR blockade enhances the control of murine melanoma growth by anti-(α)PD-1 checkpoint blockade. However, this effect was most significant when β-blocker was combined with dual αPD-1 + high dose interleukin-2 therapy and was reproduced by selective blockade of β2 ARs. These results identify a novel strategy that can be quickly introduced to potentially increase the number of patients who benefit from immune-based therapies.